Investigação do processo da aprendizagem significativa de estatística no ensino médio: um estudo com base na aplicação de uma UEPS no contexto do estado do Acre - Oliveira, Francisco Marinho de (2023)
This text refers to the master's thesis, allocated to the research line Educational Practices in the teaching of Science and Mathematics, explaining the investigation and its expectations. The study starts from the need to propose a didactic sequence for teaching statistics topics in Basic Education, starting from a meaningful perspective of learning in a local context. The urgency for this investigation is mainly due to the low performance of average proficiency in mathematics evidenced in external assessments of the Basic Education Assessment System (BEAS), and the International Student Assessment Program (ISAP). These aspects, which lead to the central question of the research expressed as follows: how does the process of meaningful learning of statistics occur in High School, through a Potentially Meaningful Teaching Units (PMTU), in the context of a Federal Institute (IF) of the state of Acre? Seeking to answer it, the present study has the general objective of investigating how the process of meaningful learning of Statistics in High School takes place through the implementation of a PMTU in the context of an IF class in the state of Acre, which addressed Statistics topics in the Technical Course Integrated to High School in Biotechnology, being organized in ten meetings and applied in a public school in the interior of Acre in the year 2023. To achieve this purpose, the PMTU was structured based on what was proposed by Moreira (2011) and whose foundations they are based on cognitivist/constructivist theories, particularly the Meaningful Learning Theory proposed by David Ausubel (1978). In addition to this basis, PMTU is guided by the use of different teaching strategies, supported by CNCB guidelines. Methodologically, the research proposed in this text is characterized as a qualitative approach, and, in relation to its objectives, as participatory research. As instruments for data collection, the following materials were used: logbook produced by the research professor, initial questionnaire with diagnostic intent, texts prepared by students, and a final questionnaire, applied during the implementation of the didactic proposal. The analysis of the data produced is limited to the ten teaching episodes, investigating in each of them evidence of signs of significant subordinate and superordinate learning. The results point to evidence of such signs, since it was noticed that the proposal made it possible to identify subsumers, promoted the construction of cognitive bridges, progressive differentiation and integrative reconciliation and enabled the transposition of the specificities of Statistics teaching to contexts different from those developed in the school environment. The Educational Product associated with this dissertation refers to a support text for high school mathematics teachers involving the PMTU implemented in the investigation. The aforementioned Educational Product is available for free access on the EduCapes Portal (http://educapes.capes.gov.br/handle/capes/741221), as well as on the program page (www.upf.br/ppgecm) and on (www.upf.br/produtoseducacionais).